2020
DOI: 10.1002/suco.202000393
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical research on the bond‐slip behavior of square‐rebar reinforced concrete during the republic of China (1912–1949)

Abstract: Square-rebar reinforced concrete structures during the republic of China (ROC) have special material properties and structural characteristics. To perform nonlinear finite element simulations of this special type of structure more accurately, a specialized bond-slip constitutive model is built.Eighteen central pullout specimens were designed based on the ROC concrete mix proportions and the square-rebar. Then, the test data were fitted with the universal global optimization method and the minimum Euclidean di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…tested 66 vintage steel rebars (30 round-rebars and 36 square-rebars), and found that, while the height of the ribs of these vintage steel rebars can meet the regulations of current standards, the space between the ribs and the relative rib area cannot. This finding indicated that the bond-slip property between vintage steel rebar and concrete might not meet the requirements of current standards, which was eventually proved by Zhang, Chun, and Jin et al (2020). Dong, Chun, and Xu et al (2017) performed an accelerated corrosion experiment on eight concrete specimens with old square-rebars.…”
Section: Introductionmentioning
confidence: 98%
“…tested 66 vintage steel rebars (30 round-rebars and 36 square-rebars), and found that, while the height of the ribs of these vintage steel rebars can meet the regulations of current standards, the space between the ribs and the relative rib area cannot. This finding indicated that the bond-slip property between vintage steel rebar and concrete might not meet the requirements of current standards, which was eventually proved by Zhang, Chun, and Jin et al (2020). Dong, Chun, and Xu et al (2017) performed an accelerated corrosion experiment on eight concrete specimens with old square-rebars.…”
Section: Introductionmentioning
confidence: 98%
“…The theoretical models and experiments in the standard [18] are all designed for round rebar components; however, according to the existing studies, the structural configuration design [23], the bond-slip behavior between rebar and concrete [24] and the rebar corrosion induced cracking model [25] for square rebar cases are very different from the round rebar cases.…”
mentioning
confidence: 99%
“…Moreover, the ratio of the critical depth and the section length of the rebars were investigated; however, they did not establish an applicable calculation method. Zhang et al [24] performed experimental and numerical investigation on the bond-slip behavior of square rebar and concrete, and the experimental results revealed that the performance was substantially weaker than that of the current deformed round rebar. Subsequently, Zhang et al [28] performed a study for experimental and theoretical analysis for the shear capacity of the square rebar reinforced concrete beam.…”
mentioning
confidence: 99%